Influence of the column web panel behaviour on the characteristics of a beam-to-column joint - Daniūnas, Alfonsas; Urbonas, Kęstutis (Journal of Civil Engineering and Management, 2013)
The paper reviews the importance of evaluation of actual joint behaviour during the design and manufacture of frame construction. The authors applied the component method, which is used in Eurocode 3. Additionally, they provided a short overview of beam-to-column joint components. The research focuses on one part of the joint-column web panel. It investigates the influence of the column web panel to the rotational stiffness and design moment resistance of the joint. The article presents several possibilities for stiffening the column web panel plate. Calculation results illustrate the influence of the characteristics of column web panel to the rotational stiffness and design moment resistance of the joint. Calculations were carried out both with an unstiffened and with a stiffened column web panel plates. The results confirmed the expected assumptions, i.e. the column web panel is an essential part of the joint, and its behaviour has a significant influence on the rotational stiffness and design moment resistance of the joint. In all calculations where column web panel was stiffened, the rotational stiffness and design moment resistance of the joint increased.